The principle of degree in modern methodological training of the future teacher of social sciences - Старєва, А. М. (Pedagogy of Higher and Secondary Education, 2012)
Staryeva A. M. The principle of degree in modern methodological training of the future teacher of social sciences. An author does actual the problem of level preparation of teacher in the context of work of new normatively legal bases in industry of higher pedagogical education of Ukraine, expresses opinion to competence-based approach in realization of methodical preparation of teacher.